Ecology of plant volatiles: taking a plant community perspective - Pierik, Ronald (2014)
Although plants are sessile organisms, they can modulate their phenotype so as to cope with environmental stresses such as herbivore attack and competition with neighbouring plants. Plant-produced volatile compounds mediate various aspects of plant defence. The emission of volatiles has costs and benefits. Research on the role of plant volatiles in defence has focused primarily on the responses of individual plants. However, in nature, plants rarely occur as isolated individuals but are members of plant communities where they compete for resources and exchange information with other plants. In this review, we address the effects of neighbouring plants on plant volatile-mediated defences. We will outline the various roles of volatile compounds in the interactions between plants and other organisms, address the mechanisms of plant neighbour perception in plant communities, and discuss how neighbour detection and volatile signalling are interconnected. Finally, we will outline the most urgent questions to be addressed in the future.